2006
DOI: 10.1093/hmg/ddi477
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the triplet repeat encoding polyglutamine within the mouse Huntington's disease gene results in subtle behavioral/motor phenotypes in vivo and elevated levels of ATP with cellular senescence in vitro

Abstract: Huntingtin (htt), the protein encoded by the Huntington's disease (HD) gene, contains a polymorphic stretch of glutamines (polyQ) near its N-terminus. When the polyQ stretch is expanded beyond 37Q, HD results. However, the role of the normal polyQ stretch in the function of htt is still unknown. To determine the contribution of the polyQ stretch to normal htt function, we have generated mice with a precise deletion of the short CAG triplet repeat encoding 7Q in the mouse HD gene (Hdh(DeltaQ)). Hdh(DeltaQ/Delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 67 publications
4
38
0
Order By: Relevance
“…Whether accumulation of these aggregates is neurotoxic or neuroprotective is still under debate since evidence also suggests that soluble mutant htt is the main toxic component (Davies et al, 1997;Saudou et al, 1998;Arrasate et al, 2004). While the expanded polyQ repeat displays pathogenic properties it is probably not essential for normal function (Clabough & Zeitlin, 2006). Mutant htt is more disposed to proteolysis and it was shown that small N-terminal htt fragments are more toxic than full length mutant htt (Cooper et al, 1998).…”
Section: Mutant Htt Gain Of Toxic Function In Hdmentioning
confidence: 99%
“…Whether accumulation of these aggregates is neurotoxic or neuroprotective is still under debate since evidence also suggests that soluble mutant htt is the main toxic component (Davies et al, 1997;Saudou et al, 1998;Arrasate et al, 2004). While the expanded polyQ repeat displays pathogenic properties it is probably not essential for normal function (Clabough & Zeitlin, 2006). Mutant htt is more disposed to proteolysis and it was shown that small N-terminal htt fragments are more toxic than full length mutant htt (Cooper et al, 1998).…”
Section: Mutant Htt Gain Of Toxic Function In Hdmentioning
confidence: 99%
“…1-4) [110]. These results suggest that enhancing selective macroautophagy may be beneficial for organisms in general, not only in the context of disease [109,110]. ER stress and autophagy regulation are closely interconnected.…”
Section: Wild Type Huntington Functionsmentioning
confidence: 84%
“…The Htt polyQ stretch does not appear to contribute to its essential functions, as its deletion in mice does not perturb embryonic development or result in motor or neuropathological deficits in adults [109]. Deletion of the polyQ stretch resulted in improved motor coordination, and a significantly increased lifespan [109,110].…”
Section: Wild Type Huntington Functionsmentioning
confidence: 99%
See 2 more Smart Citations